In silico prediction of molecular mechanisms of toxicity mediated by the leptospiral PF07598 gene family-encoded virulence-modifying proteins - Chaurasia, Reetika; Vinetz, Joseph M. (Frontiers in Molecular Biosciences, 2023)
Mechanisms of leptospirosis pathogenesis remain unclear despite the identification of a number of potential leptospiral virulence factors. Severe leptospirosis clinically manifests with vascular instability, liver and renal dysfunction, and pulmonary hemorrhage, which many postulate to be caused by toxins secreted by pathogenic Leptospira. We recently demonstrated potential mechanisms by which the VM proteins encoded by the PF07598 gene family—found only in group 1 pathogenic Leptospira—might mediate the clinical pathogenesis of leptospirosis. VM proteins have a unique AB domain architecture encoded by a single gene, different than other AB toxins, which are typically encoded by two or more genes and self-assembled into a multi-domain holotoxin. Leptospiral VM proteins are secreted R-type lectin domain-containing exotoxins with discrete N-terminal ricin B-like domains involved in host cell surface binding, and a C-terminal DNase/toxin domain involved in cytotoxicity. Here we use the artificial intelligence-based AlphaFold algorithm and other computational tools to predict and elaborate on details of the VM protein structure-function relationship. VM proteins share sequence motifs and structural similarities with castor bean-originating ricin B chains (N-terminal unique (QxW)3 motifs, aromatic patches), the Mycoplasma CARDS toxin (D3 domain, aromatic patches), and mammalian DNase I (C-terminal catalytic residues). Computation-driven structure-function studies of VM proteins will guide experimentation towards mechanistic understandings of leptospirosis pathogenesis, which underlie development of new therapeutic and preventive measures for this devastating disease.